Long-Term Visual and Neurodevelopmental Outcomes in Two Children with Congenital Nystagmus Secondary to Methadone Exposure In utero - Galli, Jessica; Loi, Erika; Franzoni, Alessandra; Accorsi, Patrizia; Micheletti, Serena; Pansera, Laura; Fazzi, Elisa (Neuropediatrics, 2023)
Methadone is used as a substitute for illicit opioids during pregnancy. However, the real effect of this molecule on visual and neurodevelopmental outcomes of the children exposed is not fully understood, since studies considered subjects born to polydrug-dependent mothers and followed for few months/years. We report the long-term outcomes of two infants with congenital nystagmus solely exposed to methadone in utero. Neurological and neurovisual evaluations were performed every year from the first year of life to 11 years of age. One child was diagnosed with developmental coordination disorder. Both cases presented with ophthalmologic (refractive errors), oculomotor (nystagmus and fixation, smooth pursuit, and saccades dysfunctions), and perceptive problems (reduced visual acuity and contrast sensitivity). While nystagmus and other oculomotor dysfunctions remained stable over time, visual acuity and contrast sensitivity improved; refractive errors worsened and required corrective lenses. Both children showed normal neurodevelopmental and cognitive profile. This report highlights the long-term visual and developmental outcomes of two children exclusively exposed to methadone underlining the possibility of a visual dysfunction and motor coordination disorder. These observations prompt the need to investigate prenatal drug exposure as a cause of congenital nystagmus.
Keywords: methadone; congenital nystagmus; pregnancy; neurovisual profile; children